Network-like DEA approach for environmental assessment: Evidence from U.S. manufacturing sectors. (15th December 2016) - Yu, Yu; Zhu, Weiwei; Shi, Qinfen; Zhang, Qian
Abstract: Environmental assessment has become an important business concern recently. On one hand, companies can invest in and implement green technology to reduce the pollution (undesirable outputs). On another hand, the companies need to simultaneously satisfy targets in both their environmental orientation and operational performance, but there is a potential conflict between operational efficiency and environmental efficiency. In order to provide an overall performance incorporating both operations and GHG emissions, we develop a network-like DEA model to combine the operational performance and environmental performance in a unified approach, considering desirable outputs and undesirable outputs respectively. First, we separate the inputs into non-managerial inputs and managerial inputs so that we can improve them by decreasing the undesirable outputs and increasing the desirable outputs simultaneously. Second, considering the potential conflict between operational efficiency and environmental efficiency, we propose a network-like DEA model to combine those two efficiencies. The key feature of this research is to provide an overall environmental assessment for capturing more managerial insights. We demonstrate the effectiveness of the proposed approach by applying it to make a firm-level overall environmental assessment in the U.S. manufacturing sector. Highlights: We separate the inputs into managerial inputs and non-managerial inputs. We develop a network-like DEA approach to provide an overall environmental assessment. We propose a unified efficiency to combine operational performance and environmental performance. Health care sector has the best-unified efficiency while the Industrials sector exhibits the lowest unified performance.